1999
DOI: 10.1094/phyto.1999.89.12.1127
|View full text |Cite
|
Sign up to set email alerts
|

Infection of Cranberry Flowers by Monilinia oxycocci and Evaluation of Cultivars for Resistance to Cottonball

Abstract: Infection of cranberry flowers by conidia of Monilinia oxycocci, the cottonball pathogen, was investigated using a squash-mount histological method. Conidia germinated on anthers, nectaries, petals, and stigmata, but not styles. The stigma was the only flower part penetrated by the fungus, but no specialized infection structures were noted. Both fungal and pollen germ tubes grew through the stylar canal and made contact with ovules and nucellar tissue by 72 h after inoculation and pollination. Cottonball incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Similar results were obtained in American cranberries in Latvia [ 12 ]. Tadych et al [ 26 ] suggest that the prevalence of this pathogen is closely related to climatic conditions, Olatinwo et al [ 10 ] associated it with a place of cultivation and McManus et al [ 27 ] associated it with different phenological stages of the plant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were obtained in American cranberries in Latvia [ 12 ]. Tadych et al [ 26 ] suggest that the prevalence of this pathogen is closely related to climatic conditions, Olatinwo et al [ 10 ] associated it with a place of cultivation and McManus et al [ 27 ] associated it with different phenological stages of the plant.…”
Section: Discussionmentioning
confidence: 99%
“…Olatinwo et al [ 10 ] reported that this pathogen is more common in ripe large cranberries before harvest, and less common in rotten berries. According to McManus [ 27 ], Phys. vaccinii can also be isolated from healthy berries (10–30%), indicating that fungal infection does not always cause disease.…”
Section: Discussionmentioning
confidence: 99%
“…fructicola (G. Winter) Honey, Monilinia laxa (Aderhold & Ruhland) Honey, and Monilinia fructigena (Aderhold & Ruhland) Honey . At least two species have been described to be important pathogens of Ericaceae: Monilinia vaccinium-corymbosi, causing mummy berry of blueberry, and Monilinia oxycocci, causing cottonball of cranberry . According to phylogenetic analyses based on rRNA sequences of Monilinia and Sclerotinia species, the separation of the genus in two sections is consistent: Junctoriae, attacking Rosaceae hosts, and Disjunctoriae, attacking Ericaceae hosts; ,, moreover, partial congruence found in the branching topologies of hosts and pathogen phylogenies led to the suggestion of cospeciation between them .…”
Section: Monilinia Spp Fungi Cause Brown Rotmentioning
confidence: 99%
“…Both are economically important pathogens in agriculture that infect hundreds of host plant species (Bolton, Thomma, & Nelson, ; Mbengue et al., ). The Sclerotiniaceae family also includes host specialist parasites such as Ciborinia camelliae that causes flower blight on Camellia (Denton‐Giles, Bradshaw, & Dijkwel, ), Sclerotinia glacialis that specifically infects Ranunculus glacialis (Graf & Schumacher, ), and Monilinia oxycocci causing the cottonball disease on cranberry (McManus, Best, & Voland, ). Other species from the Sclerotiniaceae have intermediate host range (tens of plant species) such as Sclerotinia trifoliorum , S. subarctica and S. borealis (Clarkson, Carter, & Coventry, ; Farr & Rossman, ).…”
Section: Introductionmentioning
confidence: 99%